Integrating Foresight and Feedback Systems for Adaptive Health Governance: A Case Study of Jeneponto Regency, Indonesia - Sakawati, Herlina; Fitri, Anisa; Widyawati, Widyawati; Haerul, Haerul; Agustina, Nina (Universitas Negeri Makassar, 2025)
The changing global health landscape demands a healthcare system that is not only responsive to crises but also has anticipatory capabilities through data-driven, adaptive, and long-term governance. This study aims to analyze the dynamics of the Foresight System and Feedback System in healthcare governance in Jeneponto Regency, South Sulawesi, as a representation of the application of the anticipatory governance concept at the regional level. The study used a qualitative approach with a case study design, involving in-depth interviews with Health Office officials and heads of community health centres, as well as analysis of secondary documents such as the 2024–2026 Health Office Strategic Plan and the Community Satisfaction Index report. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data condensation, data presentation, and drawing and verifying conclusions. The results show that the capacity of the Foresight System in Jeneponto Regency is still limited to administrative reporting functions and has not yet played a role as an anticipatory system in predicting health risks based on epidemiological trends. Meanwhile, the Feedback System demonstrates progress toward an adaptive evaluation model, with four of the five key performance indicators improving, although the speed of response to critical health risks, such as maternal mortality, remains suboptimal. Key barriers include fragmented health information systems, limited analytical capacity, and weak integration across digital platforms such as SIMPUS, e-Puskesmas, and SKDR. This study confirms that simultaneous integration of the Foresight System and Feedback System is necessary to build an anticipatory and responsive health governance cycle at the regional level.